2001
DOI: 10.1207/s15327825mcs0403_02
|View full text |Cite
|
Sign up to set email alerts
|

On the Deceptive Effectiveness of Labeled and Unlabeled Advertorial Formats

Abstract: This experiment investigates the effects of an advertorial message on 4 dimensions of reader involvement. The use of the advertorial format was found to have increased participants' perceived message relevance, attention to written message, message elaboration, and message recall over the use of a standard advertisement format. Responses to labeled and unlabeled versions of the same advertorial did not vary significantly. Although participants perceived both labeled and unlabeled advertorials to be advertiseme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(80 citation statements)
references
References 21 publications
(26 reference statements)
3
73
1
3
Order By: Relevance
“…This is explained by the idea that readers believe that feature ads are less credible and therefore they spend less effort processing the content of these ads (Cameron & Curtin, 1995). A few years later, however, Kim, Pasadeos, and Barban (2001) found no significant differences between labeled and unlabeled advertorials regarding self-reported attention paid to the message, message elaboration (measured with thought listing), and their recall of message content.…”
Section: Attention To Sponsored Contentmentioning
confidence: 77%
See 2 more Smart Citations
“…This is explained by the idea that readers believe that feature ads are less credible and therefore they spend less effort processing the content of these ads (Cameron & Curtin, 1995). A few years later, however, Kim, Pasadeos, and Barban (2001) found no significant differences between labeled and unlabeled advertorials regarding self-reported attention paid to the message, message elaboration (measured with thought listing), and their recall of message content.…”
Section: Attention To Sponsored Contentmentioning
confidence: 77%
“…In their experiment on labeling advertorials, Kim, Pasadeos, and Barban (2001) found that 29% of the participants who were exposed to a labeled advertorial could actually recall this label.…”
Section: Disclosure Awarenessmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the practice of native advertising blurs the frames surrounding what appears to be editorial and what is promotional content, readers are less likely to recognize that they are being exposed to advertising (Carlson 2015;Conill 2016;Howe and Teufel 2014;Sonderman and Tran 2013). Even when efforts are made to be transparent, research has shown that people often do not notice paid advertising labels whether in print or online environments (Cameron 1 4;Gilley 2013;Kim et al 2001;Wojdynski and Evans 2016). Furthermore, even when labels such as "sponsored content" are clearly applied, a majority of people do not understand what the word "sponsored" is supposed to mean (Gilley 2013).…”
Section: Persuasion Knowledge Modelmentioning
confidence: 99%
“…Todavia, esses parcos estudos verificaram, por exemplo, que a atenção aumenta quando o placement tem um formato mais editorial ao invés de um formato mais comercial (Kim, Pasadeos, & Barban, 2001;Lord & Putrevu, 1998;Reijmersdal, Neijens, & Smit, 2005). No entanto, ressalta-se que todos os estudos preocupados com a atenção no placement utilizaram questionários para a mensuração do construto.…”
Section: Atenção (Visual)unclassified